Evaluating capacity building of the local community towards environmental conservation in an estuarine community, Kong Kong Laut, Johor - Mohd Kusin, Faradiella; Md Joni, Amirul Azuan; Mohamat Yusuff, Ferdaus; Syed Hasan, Sharifah Nur Munirah (Malaysian Institute of Planners, 2019)
Key community-based environmental conservation programmes in Kong Kong Laut, Johor include the river and mangrove ecosystem conservation and management programme. The overall aim of conserving the ecosystem and encouraging local community participation in the programme is to promote the existing eco-tourism potential of the area. This paper entails the outcomes of community-based activities aimed at building the capacities of local communities through community mobilisation, awareness creation and capacity building (i.e. transferred knowledge and skills). Findings indicate that there have been improvements in the river water quality status within the ecosystems over the course of a one-year project, despite relatively small participation among the local communities in the conservation programme. However, it was evident that active participation from a minority group of the local community has contributed to significant human and social capital, suggesting that community empowerment might be crucial for future development. Despite this, a school outreach programme on waste minimisation within the community demonstrated an encouraging level of participation among school children and teachers. The major challenge to maintaining continuous efforts to conserve their environment is the simultaneous developments taking place close to the river and mangrove ecosystems. While it remains a challenge to all the stakeholders, collaborative efforts among the local communities and the university, school, government agencies and private sector have made it possible to strategise for more future approaches that will benefit the whole community.